The determinants of accounting fraud tendency - Predita Arie Ayu Putri; Soni Agus Irwandi (STIE Perbanas Surabaya, 2016)
This study aims to retest the effect of internal control effectiveness, compensation system suitability, and information asymmetry, adherence to accounting rules, and management morality on accounting fraud tendency. This study uses agency theory and fraud triangle as a grand theory. This study was conducted in 19 companies in Surabaya with 79 managers as respondents. The data were analyzed using multiple linear regression models with SPSS software. The results show that internal control effectiveness, compensation system suitability, information asymmetry, adherence to accounting rules, and management morality have a significant effect on accounting fraud tendency.